DESAIN MEDIA PEMBELAJARAN BERBASIS SMARTPHONE ANDROID MENGGUNAKAN ADOBE FLASH CS 6 PADA MATA PELAJARAN SISTEM OPERASI KOMPUTER SMK GUNUNG SARI 1 MAKASSAR - Ashabul Taufik; Andi Muh. Akbar Saputra (Jurnal Publikasi Teknik Informatika, 2023)
This study aims to find out how to design Android smartphone learning media and the feasibility level of Android smartphone learning media in computer operating system subjects. This study uses the Research and Development research method, using the 4D development model, namely Define, contains activities to determine what products will be developed, along with their specifications. This stage is a needs analysis activity, carried out through research and literature studies. Design (Design), contains activities to create a design for a predetermined product. Development (Development), contains the activities of making a design into a product and testing the validity of the product repeatedly until a product is produced according to predetermined specifications. Dessemnation (Dissemination), contains the activities of disseminating products that have been utilized by others. The production stage produces the initial product which is then reviewed by material experts and media experts. The results of the review were revised according to the suggestions of the two experts. In the evaluation stage, the product being tested on students, the test subject was a class X TKJ SMK Gunung Sari 1 Makassar. Data is obtained by price, scores are given on a scale of 1-4. The results obtained from the validation of media experts were 78.33%, and the validation results from material experts were obtained 92.30%, with an average proportion of the two validators being 85.31%. The results of the small trial were in the good category with a proportion of 100%, then the large group trial was 75% in the good category with a frequency of 12 people, then 25% in the fairly good category with a frequency of 4 people. Based on these results, learning media for Android smartphones using Adobe Flash CS6 get a good view of being used as learning media. Thus it can be concluded that the learning media product based on an Android smartphone using Adobe Flash CS6 has complied with research and development principles and is well used in the learning process for class X SMK TKJ SMK Gunung Sari 1 Makassar